Association of accelerometer-derived step volume and intensity with hospitalizations and mortality in older adults: A prospective cohort study - Asier Mañas; Borja del Pozo Cruz; Ulf Ekelund; José Losa Reyna; Irene Rodríguez Gómez; José Antonio Carnicero Carreño; Leocadio Rodríguez Mañas; Francisco J. García García; Ignacio Ara (Elsevier, 2022)
Purpose: This study aimed to examine the associations of accelerometer-derived steps volume and intensity with hospitalizations and all-cause mortality in older adults. Methods: This prospective cohort study involved 768 community-dwelling Spanish older adults (78.8 ± 4.9 years, mean ± SD; 53.9% females) from the Toledo Study for Healthy Aging (2012-2017). The number of steps per day and step cadence (steps/min) were derived from a hip-mounted accelerometer worn for at least 4 days at baseline. Participants were followed-up over a mean period of 3.1 years for hospitalization and 5.7 years for all-cause mortality. Cox proportional hazards regression models were used to estimate the individual and joint associations between daily steps and stepping intensity with hospitalizations and all-cause mortality. Results: Included participants walked 5835 ± 3445 steps/day with an intensity of 7.3 ± 4.1 steps/min. After adjusting for age, sex, body mass index (BMI), education, income, marital status and comorbidities, higher step count (hazard ratio (HR) = 0.95, 95% confidence interval (95%CI: 0.90-1.00, and HR = 0.87, 95%CI: 0.81-0.95 per additional 1000 steps) and higher step intensity (HR = 0.95, 95%CI: 0.91-0.99, and HR = 0.89, 95%CI: 0.84-0.95 per each additional step/min) were associated with fewer hospitalizations and all-cause mortality risk, respectively. Compared to the group having low step volume and intensity, individuals in the group having high step volume and intensity had a lower risk of hospitalization (HR = 0.72, 95%CI: 0.52-0.98) and all-cause mortality (HR = 0.60, 95%CI: 0.37-0.98). Conclusion: Among older adults, both high step volume and step intensity were significantly associated with lower hospitalization and all-cause mortality risk. Increasing step volume and intensity may benefit older people.